Ovarian Steroids Regulate Gene Expression in the Dorsal Raphe of Old Female Macaques - Bethea, Cynthia L. (Neurobiol Aging, 2015)
With extended lifespans in modern humans, menopause has become a significant risk factor for depression, anxiety, loss of cognitive functions, weight gain, metabolic disease, osteoporosis, cardiovascular disease and neurodegenerative diseases. Clinical studies have found beneficial neural effects of ovarian steroid hormone therapy (HT) during the menopausal transition and data are emerging that it can be continued long-term. To further understand molecular underpinnings of the clinical studies, we used qRT-PCR to examine gene expression in the serotonergic dorsal raphe of old (>18 yrs) rhesus macaques, focusing on genes related to depression, cellular resilience and neurodegenerative diseases. The animals were ovariectomized (Ovx, surgically menopausal) and subjected to either estradiol or estradiol plus progesterone HT, or to placebo, starting 2 months after Ovx and continuing for ~4 years. Significant changes were observed in 36 out of 48 genes examined that encode proteins supporting serotonin neurotransmission, synapse assembly, glutamate neurotransmission, DNA repair, chaperones, ubiquinases and transport motors, as well as genes encoding proteins that have potential to delay the onset of neuropathologies. The data reveal important gene targets for chronic HT that contribute to neural health. Alternatively, the loss of ovarian steroids may lead to loss of functions at the gene level that contribute to many of the observable neural deficits following menopause.